The unfolding and attempted refolding of mitochondrial aspartate aminotransferase from pig heart. - West, S M (1990)
The unfolding of the mitochondrial isoenzyme of aspartate aminotransferase from pig heart in solutions of guanidinium chloride (GdnHCl) has been studied. By a number of criteria (enzyme activity, protein fluorescence, c.d., thiol-group reactivity), the enzyme was judged to be almost completely unfolded in 2 M-GdnHCl. On dilution of the GdnHCl, no re-activation of the enzyme could be observed, whether or not pyridoxal 5'-phosphate and dithiothreitol were present. The behaviour of the mitochondrial isoenzyme is in marked contrast with that of the cytoplasmic isoenzyme [West & Price (1989) Biochem. J. 261, 189-196], despite the similarities in the amino acid sequences and tertiary structures of the two isoenzymes. The implications of these findings for the process of folding and assembly of the mitochondrial isoenzyme in vivo are discussed.